Uncommon and peculiar soft tissue sarcomas: Multidisciplinary review and practical recommendations. Spanish Group for Sarcoma research (GEIS –GROUP). Part II. (September 2021) - Martínez-Trufero, Javier; Cruz Jurado, Josefina; Hernández-León, C.Nieves; Correa, Raquel; Asencio, Jose Manuel; Bernabeu, Daniel; Alvarez, Rosa; Hindi, Nadia; Mata, Cristina; Marquina, Gloria; Martínez, Virginia; Redondo, Andres; et al.
Graphical abstract: Highlights: General guidelines for sarcomas are of limited value and not applicable for some uncommon sarcomas. Specific differential characteristics of uncommon sarcomas imply specific clinical approaches. New targeted therapies give new opportunities in alveolar uncommon soft tissue sarcomas. Genomic sequencing is expanding our molecular knowledge of potential targets in sarcomas. These improvements may change natural history of tumours like NTRK-rearrangement sarcomas. Abstract: Among all Soft Tissue sarcomas there are some subtypes with low incidence and/or peculiar clinical behaviour, that need to be consider separately. Most of them are orphan diseases, whose biological characteristics imply a clearly different diagnostic and therapeutic approach from other more common sarcoma tumors. We present a brief and updated multidiciplinary review, focused on practical issues, aimed at helping clinicians in decision making. In this second part we review these subtypes: Alveolar Soft Part Sarcoma, Epithelioid Sarcoma, Clear Cell Sarcoma, Desmoplastic Small Round Cell Tumor, Rhabdoid Tumor, Phyllodes Tumor, Tenosynovial Giant Cell Tumors, Myoepithelial Tumor, Perivascular Epithelioid Cell Neoplasms (PEComas), Extraskeletal Myxoid Chondrosarcoma, NTRK-fusions Sarcomas. Most of them present their own radiological and histopathological feautures, that are essential to know in order to achieve early diagnosis. In some of them, molecular diagnosis is mandatory, not only in the diagnosis, but also to plan the treatment. On the other hand, and despite the low incidence, a great scientific research effort has been made to achieve new treatment opportunities for these patients even with approved indications. These include new treatments with targeted therapies and immunotherapy, which today represent possible therapeutic options. It is especially important to be attentive to new and potential avenues of research, and to promote the conduct of specific clinical trials for rare sarcomas.